Evaluating Birth Outcomes From a Community-Based Pregnancy Support Program for Refugee Women in Georgia - Elizabeth A. Mosley; Elizabeth A. Mosley; Michelle Pratt; Ghenet Besera; Lasha S. Clarke; Heidi Miller; Tracy Noland; Bridget Whaley; Jennifer Cochran; Amber Mack; Melinda Higgins (Frontiers Media S.A., 2021)
Refugee women face numerous and unique barriers to sexual and reproductive healthcare and can experience worse pregnancy-related outcomes compared with U.S.-born and other immigrant women. Community-based, culturally tailored programs like Embrace Refugee Birth Support may improve refugee access to healthcare and health outcomes, but empirical study is needed to evaluate programmatic benefits. This community-engaged research study is led by the Georgia Doula Access Working Group, including a partnership between academic researchers, Emory Decatur Hospital nurses, and Embrace. We analyzed hospital clinical records (N = 9,136) from 2016 to 2018 to assess pregnancy-related outcomes of Embrace participants (n = 113) and a comparison group of women from the same community and racial/ethnic backgrounds (n = 9,023). We controlled for race, language, maternal age, parity, insurance status, preeclampsia, and diabetes. Embrace participation was significantly associated with 48% lower odds of labor induction (OR = 0.52, p = 0.025) and 65% higher odds of exclusive breastfeeding intentions (OR = 1.65, p = 0.028). Embrace showed positive but non-significant trends for reduced cesarean delivery (OR = 0.83, p = 0.411), higher full-term gestational age (OR = 1.49, p = 0.329), and reduced low birthweight (OR = 0.77, p = 0.55). We conclude that community-based, culturally tailored pregnancy support programs like Embrace can meet the complex needs of refugee women. Additionally, community-engaged, cross-sector research approaches could ensure the inclusion of both community and clinical perspectives in research design, implementation, and dissemination.